2021
DOI: 10.3390/molecules26092697
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and Chemical Characteristic of Two Insect Species: Tenebrio molitor and Zophobas morio Larvae Affected by Roasting Processes

Abstract: The volatile compounds from insects (Tenebrio molitor and Zophobas morio larvae) roasted at 160, 180, or 200 °C and fed with potato starch or blue corn flour were isolated by solid-phase microextraction (SPME), and identified by gas chromatography–mass spectrometry (GC-MS). In the tested material, 48 volatile compounds were determined. Among them, eight are pyrazines, aroma compounds that are formed in food products during thermal processing due to the Maillard reaction. Eleven of the identified compounds infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Convection oven treatment (180 • C, 5min) led to roasted shrimp-like odour characteristics attributed to intermediates of both Maillard reaction and lipid oxidation, such as pyrazines, ketones, alcohols and aldehydes [73]. Likewise, Zołnierczyk et al (2021) [74] reported increased pyrazine levels in larvae baked between 160-200 • C. In sensory analysis, these larvae were evaluated as having burnt, toasted bacon and bread-like flavours. These observations highlight how industrial processes involved in the production of mealworm products may affect the volatile quality of the final product.…”
Section: Discussionmentioning
confidence: 99%
“…Convection oven treatment (180 • C, 5min) led to roasted shrimp-like odour characteristics attributed to intermediates of both Maillard reaction and lipid oxidation, such as pyrazines, ketones, alcohols and aldehydes [73]. Likewise, Zołnierczyk et al (2021) [74] reported increased pyrazine levels in larvae baked between 160-200 • C. In sensory analysis, these larvae were evaluated as having burnt, toasted bacon and bread-like flavours. These observations highlight how industrial processes involved in the production of mealworm products may affect the volatile quality of the final product.…”
Section: Discussionmentioning
confidence: 99%
“…The defatted tiger nut flour contains abundant sugars and amino acids, which can be used as suitable flavor precursors [5,10]. Proper baking condition can retain the flavor of defatted tiger nut flour, increasing the sweet, caramel, and nutty flavors as well as special aromas such as floral and fruity [12]. This makes up for the deficiency of reduced flavor of the flour after defatting, increasing its popularity among consumers and the range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic aroma of roasted insects is influenced by pyrazines and carbonyl compounds that are formed (by Maillard reaction) during heat treatment, in particular from 11 odorous compounds that give the typical aroma of traditional European baked dishes, such as bread, potatoes, meat (Żołnierczyk & Szumny, 2021). Therefore, it is essential to choose the right cooking conditions.…”
Section: Nutritional and Economic Value Of Tenebrio Molitormentioning
confidence: 99%
“…Therefore, it is essential to choose the right cooking conditions. In their recent study, Żołnierczyk & Szumny (2021) found that mealworms roasted at 180 • C had a pleasant and desirable smell of bread while cooking at a higher temperature (200 • C) imparted an undesirable burning smell. Fur-thermore, according to this study, the sensory characteristics of roasted TML are not influenced by the type of feed.…”
Section: Fatty Acidsmentioning
confidence: 99%